The Description of II Class Women Prisoners Cervix in Semarang - Erna Kusumawati; Novita Nining Anggraini (Universitas Muhammadiyah Semarang, 2016)
Abstract. The second highest cancer in the world is cervix. The early detection of cervix was done in order to give the description about pathophysiology, the risk, the symptoms, the invention of lesion of cancer, and treat them. The prisoners often faced the obstacle in doing the adaptation to the prisons environment. The longer isolation in the prison made the improvement of doing homosexual done by someone. It influenced to the cervix health that enabled traumatic.Besides that, the condition of the prison with bad sanitation and environment could decrease the quality of prisoners life,facilitate the spread of health problems like TBC, HIV/AIDS. The method of this research was descriptive. The population was 44 women prisoner of class IIB in which two of them were infected by HIV. Speculum examination was done to the women prisoners. The result of this study showed that the test of positive IVA was 27.3% (12 women), the negative IVA was 72.7% (32 women), the partio erosion was 34.1% (15 women), the un partio erosion was 65.9% (29 women), whitish translucent was 36.4% (16 women) consisted of whitish was 54.5% (24 women), yellowish was 6.8% (3 women), and greenish was 2.3% (1 woman). From the result above, it could be concluded that the description of II class womens cervix in the prison was not health physically.